MENINGKATKAN KEGIATAN MENGANYAM UNTUK MENINGKATKAN MOTORIK HALUS ANAK KELOMPOK B DI TK MUTIARA HATI - Hasanah, Qudwatun; Rachmayani, Ika; Nada Buahana, Baiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the fine motor skills of Group B children at Mutiara Hati Kindergarten through weaving activities. The study employed the Classroom Action Research (CAR) method, conducted over three cycles. The subjects consisted of 10 children from Group B. Data collection was carried out through observation and documentation, while data analysis utilized quantitative descriptive analysis. In Cycle I, the implementation rate of the weaving activity reached 81.25%, while the children's fine motor skills reached 36.66%, falling into the